INCREASING CHILDREN'S CONSCIOUSNESS IN MOTORCYCLING OF MOTORCYCLE ON RAILWAY (study in Demak Regency) - Ida Musofiana; Rizki Adi Pinandito (UNISSULA, 2017)
Traffic accidents are a global health problem. The number of traffic accidents each year has increased and traffic accidents in Indonesia are assessed by the World Health Organization (WHO) as the third killer after heart disease and tuberculoces. This study aims to examine how exactly the level of knowledge of parents in Demak District to their children who ride motorcycles on the highway. The method used in this research is descriptive qualitative, with research location in Demak Regency. In order to obtain data in the field, data collection techniques such as observation and structured interviews, and using data analysis. The role of parents as a mentor is accompanying children while driving, and monitor the child if you want to ride a motorcycle, check the safety of driving. The purpose of this research is to become the agenda of socialization of safety riding for the general public in order to increase awareness of the importance of maintaining traffic safety on the highway, and reminding each other if there is violation of traffic rules. One of them reprimanded underage riders so as not to speed-kebutan or more careful.